Canon of the regular order of Saint Anthony of Vienna, in city habit - Giffart, Pierre François, b. 1677 (engraver):::Creator::::::::::::; Hélyot, Pierre Hippolyt, 1660-1716:::Contributor:::::::::::: (Louis)
Engraving of a Canon of the regular order of Saint Anthony of Vienna, in city habit